Transient Lipid-Protein Structures and Selective Ganglioside Uptake During α-Synuclein-Lipid Co-aggregation - Gaspar, Ricardo; Idini, Ilaria; Carlström, Göran; Linse, Sara; Sparr, Emma (Frontiers in Cell and Developmental Biology, 2021)
α-Synuclein is a membrane-interacting protein involved in Parkinson’s disease. Here we have investigated the co-aggregation of α-synuclein and lipids from ganglioside-containing model membranes. Our study relies on the reported importance of ganglioside lipids, which are found in high amounts in neurons and exosomes, on cell-to-cell prion-like transmission of misfolded α-synuclein. Samples taken along various stages of the aggregation process were imaged using cryogenic transmission electron microscopy, and the composition of samples corresponding to the final state analyzed using NMR spectroscopy. The combined data shows that α-synuclein co-assembles with lipids from the ganglioside (GM1)-containing model membranes. The lipid-protein samples observed during the aggregation process contain non-vesicular objects not present at the final stage, thus capturing the co-existence of species under non-equilibrium conditions. A range of different lipid-protein co-assemblies are observed during the time course of the reaction and some of these appear to be transient assemblies that evolve into other co-aggregates over time. At the end of the aggregation reaction, the samples become more homogeneous, showing thin fibrillar structures heavily decorated with small vesicles. From the NMR analysis, we conclude that the ratio of GM1 to phosphatidyl choline (PC) in the supernatant of the co-aggregated samples is significantly reduced compared to the GM1/PC ratio of the lipid dispersion from which these samples were derived. Taken together, this indicates a selective uptake of GM1 into the fibrillar aggregates and removal of GM1-rich objects from the solution.